If crime novels were actual criminal cases - Lozanova, Ina (Law Journal of New Bulgarian University, 2021)
The current article aims to present a hypothetical review of some legal omissions in selected, reader-favorite crime novels. The material is based on legal principles which are common to states governed by the rule of law, and it would be useful to students of law and other academic courses. The presented cases in works of fiction have been analyzed from the standpoint of the acting Bulgarian penal law and Criminal Procedure Code.